Differential remodeling of subchondral bone plate and trabecular bone of the tibia in spontaneous animal models of osteoarthritis - Zamli, Zaitunnatakhin; Talib, Nurul Ain Aisyah; Akman, Akma Azmiera (2018)
Osteoarthritis (OA) is a degenerative joint disease. In the knee OA, several joint changes were observed and among these include articular cartilage (AC) degeneration, and subchondral bone (Sb) remodeling. Despite of extensive experimental and clinical studies, the role of bone remodeling in the two sub-regions of Sb, i.e. the subchondral bone plate (Sbp) and trabecular bone (Tb), during the initiation and development of OA has yet to be determined. Hence, this study aims to determine the rate of Sbp and Tb remodeling in Dunkin Hartley (DH) guinea pigs at 10, 20 and 30 weeks of age. To achieve this aim, the Sb remodeling parameters and AC degeneration were assessed in the medial and lateral side of the tibia by using histomorphometric and histological techniques, respectively. The data showed that the AC degeneration was more pronounced in the medial than the lateral side, and worsen with ageing. At 30 weeks of age, the percentage of mineralizing surface (MS) of Sbp was higher in the medial than the lateral (medial: 4.17 ± 0 %, lateral: 4.17 ± 0 %). In contrast, the MS, mineral apposition rate (MAR) and bone formation rate (BFR) of Tb was decreased at the final time point and significantly greater in the lateral than the medial side of the tibia. Taken together, the above findings suggest that the decrease of Tb remodeling was due to stress-shielding effects as a result of Sbp thickening and hypermineralization.